Heraclitus and Hippocrates: the Paradigm of the Elements - Čiurlionis, Jonas (Problemos, 2021)
The article analyses the remaining fragments and testimonies of Heraclitean philosophy and their connection with Hippocratic medicine. It is claimed that both schools belong to the same philosophical-scientific paradigm of the elements. Therefore, theoretical insights of the school of Cos might well serve explaining complicated and often difficult to interpret Heraclitean thoughts. Moreover, it is plausible that parts of Corpus Hippocraticum were written under the influence of the Heraclitean philosophy and therefore its analysis and interpretative application allows us to partially reconstruct the fragmented Heraclitean ideas into the single unified system. The article uses comparative analysis of both thinking traditions in regard to psychological, ethical, physiological, cosmological, and medical ideas. Similarities in explaining human nature are revealed. It is shown that science (medicine) and philosophy in Antiquity use the same paradigmatic utterances to describe reality. Therefore, there are many mutual interconnecting principles between early philosophy and medicine.